2021
DOI: 10.1029/2020jd034217
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed, Multi‐Scale Assessment of an Atmospheric River Event and Its Impact on Extreme Glacier Melt in the Southern Alps of New Zealand

Abstract: North‐westerly airflow and associated atmospheric rivers (ARs) have been found to profoundly influence New Zealand’s west coasts, by causing flooding, landslides and extreme ablation and accumulation on glaciers in the Southern Alps. However, the response of local glacier mass balance to synoptic‐scale circulation, including events with ARs, has typically not been investigated by considering mesoscale processes explicitly. In this study, high‐resolution atmospheric simulations from the Weather Research and For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 128 publications
(276 reference statements)
1
5
0
Order By: Relevance
“…Several studies have suggested a link between intense NE Greenland melt events and warm, dry downslope winds known as "foehn" descending from the GrIS plateau to the west 3,[20][21][22] . Mattingly et al 21 found evidence that atmospheric rivers (ARs) affecting northwest (NW) Greenland may lead to foehn conditions and enhanced melt in NE Greenland after the moist air mass crosses the ice divide and flows downslope, similar to warming documented on the lee side of the West Antarctic peninsula and other mountainous areas [23][24][25][26] . However, there has not been any systematic study of the role of foehn in forcing melt in northern Greenland, where the topography consists of a wide dome with a relatively gentle slope in comparison with the more narrow mountain ranges studied in other regions.…”
mentioning
confidence: 99%
“…Several studies have suggested a link between intense NE Greenland melt events and warm, dry downslope winds known as "foehn" descending from the GrIS plateau to the west 3,[20][21][22] . Mattingly et al 21 found evidence that atmospheric rivers (ARs) affecting northwest (NW) Greenland may lead to foehn conditions and enhanced melt in NE Greenland after the moist air mass crosses the ice divide and flows downslope, similar to warming documented on the lee side of the West Antarctic peninsula and other mountainous areas [23][24][25][26] . However, there has not been any systematic study of the role of foehn in forcing melt in northern Greenland, where the topography consists of a wide dome with a relatively gentle slope in comparison with the more narrow mountain ranges studied in other regions.…”
mentioning
confidence: 99%
“…Despite the deficiency in modeled surface albedo, the statistical performance metrics are predominantly in the range of previous model evaluations of hourly WRF simulations (e.g., Hines and Bromwich, 2008; Bromwich et al ., 2009; Collier et al ., 2018; Temme et al ., 2020; Turton et al ., 2020; Kropač et al ., 2021), suggesting sufficient model skill to use the model output in the further analyses of the cloud effect.…”
Section: Resultsmentioning
confidence: 99%
“…The model was run for 22 days, covering the period July 21 to August 10, 2019. The first 48 hr were discarded for model spin‐up in accordance with previous WRF model studies (e.g., Listowski and Lachlan‐Cope, 2017; Kropač et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Glacier retreats have complex impacts on the ecosystem, water cycle and underground stress. (1) The decrease of glacier reduces the ground surface stress, thus changing the balance between underground stress and surface pressure. For glaciers located in the tectonic shear zone, this may cause fault earth.…”
Section: Discussionmentioning
confidence: 99%